Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1081/pln-100103669
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of Container-Grown Christmas Cacti

Abstract: The effect of nitrogen (N), phosphorus (P), potassium (K) and lime additions to container-grown Schlumbergera x buckleyi were examined in two experiments. In each case rooted cuttings were grown in peataperlite (1:1, vav), with three plants per pot, for 17 months in a heated greenhouse. Foliage growth and¯ow-ering were strongly enhanced by added N and fertilization of between 1800 and 2200 g N m 73 (105±130 g N m 73 per month) and a foliar N content of 3.4±4.2% were recommended. Flowering was delayed by high N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This may be the result of an ecological push to reproduce when the environment becomes less favorable or in response to a seasonal change as in low‐temperature–induced flowering (Ali and Lovatt, 1995). Excess N may result in either no effect (Schultheis and Dufault, 1994) or in a delay of duration, magnitude, and time to flowering (Spurway and Thomas, 2001). Others have reported decreased time to flowering under N deficiency (Xu et al, 2001; Kostenyuk et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…This may be the result of an ecological push to reproduce when the environment becomes less favorable or in response to a seasonal change as in low‐temperature–induced flowering (Ali and Lovatt, 1995). Excess N may result in either no effect (Schultheis and Dufault, 1994) or in a delay of duration, magnitude, and time to flowering (Spurway and Thomas, 2001). Others have reported decreased time to flowering under N deficiency (Xu et al, 2001; Kostenyuk et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrate application in concentrations of 0.8; 4 or 16 mM N on Opuntia fícus-indica also did not reflect the growth of the species; however Nerd & Nobel (1995) related the increase of nitrate internal concentrations in plants as a reserve for the growth of new vegetative organs (luxury consumption). Spurway & Thomas (2001), studying the effect of N in growth and flowering of epiphytic cactus (Schlumbergera x buckleyi), observed that in the absence of N the plants showed chlorosis, smaller size and flowering; at intermediate doses (2,370 g N/m 3 /month) an increase of growth and flowering occurred, whereas high doses of N contributed to growth inhibition when compared to control (-19.7% of dry matter weight) and delayed flowering. The species of cacti submitted to nitrogen fertilization with 8-16 mM N increased photosynthesis, with an increase of CO 2 absorption in approximately 400% (Nobel & Barrera, 2004).…”
Section: Resultsmentioning
confidence: 99%